IMPLEMENTASI KEBIJAKAN PENGEMBANGAN PARIWISATA SEJARAH OLEH DINAS PARIWISATA PEMUDA DAN OLAHRAGA KABUPATEN SIAK TAHUN 2012-2014 - Yophi Salrahmanda; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study was conducted to explain the implementation of the Tourism Development Policy made the Department of Tourism in particular Siak district government policies regarding Local Regulation No. 12 Year 2012 on Tourism Development Master Plan In Siak. As for the background of this research is the implementation of the policy has not been well. This study uses the theory of public policy implementation that emphasizes the approach of George Edward III in order to explain the phenomena encountered in the field. This study used qualitative methods, while the technique of data collection using interviews, observation and discussion with sources of research. Furthermore, the data in the form of data qualitative and quantitative data were analyzed with descriptive technical data analysis. The results showed that the actors implementing the policy has not been able to implement the policy properly due to lack of human resources who are competent in doing development. In addition, the lack of historical attractions that can be enjoyed as long as the government through the Department of Tourism only do maintenance to historic buildings not do more development to improve the quality of the attraction. Coupled with the lack of tourist facilities in Siak Regency as a souvenir sales. So that this condition makes tourism Siak can not be a reliable sector becomes self Siak. The results also indicate that the scope of the social interaction between communities, employers and the government has not been established. This of course have an impact on the political sphere public support for the policy. While the economic sphere also no significant effect on the increase in local revenues and increase social welfare.Keywords: history Tourism and Policy Implementation